The association between dual sensory impairment and social participation among older adults in China: a moderated mediation model of activities of daily living and depressive symptoms - Lunxin Liu; Zhenglin Cao; Qingshan MA; Zhiliu Liao (BMC Geriatrics)
Abstract Background While dual sensory impairment (DSI) is known to reduce social participation (SP) in older adults, the underlying mechanisms remain unclear. Therefore, the aim of this study was to ascertain: (1) whether ADL mediates the relationship between DSI and SP, and (2) how depressive symptoms modify the mediation pathway - questions essential for developing targeted interventions. Methods In the 2018 wave of the China Health and Retirement Longitudinal Study (CHARLS), 8,270 older individuals (60 years of age or older) were enrolled. We examined a mediation model first, where ADL was a mediator between DSI and SP. Furthermore, depressive symptoms were integrated into the model as moderator in the correlation between DSI and ADL. The PROCESS macro was used to analyze the mediation and moderated mediation models. Results In older people, DSI correlated negatively with SP, and ADL partially mediated this association (B = -0.019, 95% CI = -0.025, -0.015) with an intermediary effect of 14.6%. Besides, the relationship between DSI and ADL was moderated by depressive symptoms (B = 0.092, 95% CI = 0.060, 0.123), and ADL was more affected by DSI in older adults who experienced higher levels of depressive symptoms. Conclusions Depressive symptoms moderated the mediation of ADL on an indirect, negative correlation between DSI and SP. The findings contribute to existing knowledge by illustrating the fundamental mechanisms connecting DSI and SP. These Findings highlight the need for integrated interventions targeting both sensory impairment and mental health to mitigate SP decline in aging populations.